A TRANSACTION COST APPROACH TO THE CHOICE OF OVERSIGHT GOVERNANCE STRUCTURES AT THE UNITED NATIONS: THE CASE OF THE INQUIRY COMMITTEE INTO THE OIL-FOR-FOOD PROGRAMME SCANDAL - Da Veiga, M. R. (2015)
A scandal of fraud and corruption in the management of the Oil-for-Food Programme for Iraq unfolded in early 2004 at the United Nations. The Secretary-General Annan, terminated the ongoing investigation of the scandal by the extant Office of Internal Oversight empowered by the General Assembly, and, with the endorsement of the Security Council, contracted out an Inquiry Committee to investigate the administration and management of the Programme. The lack of reasonable number of studies about internal audit in its natural settings (Lee, 2004), aggravated by the gaps found in the literature about the impact of pathological behavior in international organizations (Barnett and Finnemore, 1999), stress the research opportunity. A longitudinal historical narrative analytical case based research applying first time Williamson’s (1999) Transaction Cost Economics theory to explore “probity” and “independence” transactions’ attributes enhanced with the “virtues ethics” McCloskey’s (2006) framework, is developed to respond to the questions i) Has the inquiry worked? ii) Has Transaction Cost Economics’ discriminating alignment hypothesis been verified in the case of the Oil-for-Food scandal inquiry? The inquiry, which contains “sovereign” as well as “quasi-judiciary” transactions elements, and though lack the “authority of the sovereign” and the “independence” of the judiciary attributes, did not work. Transaction Cost Economics alignment hypothesis did not verify and “probity” hazards – “ethics” – cannot be relieved by governance structures, i.e., incentives. I argue that Transaction Cost Economics should be modified to include McCloskey’s “virtues ethics” behavioral dimension as a transaction costs’ reduction device and an explanatory framework for bureaucratic ethical failures.